Peptidomimetics I - Lubell, William D.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The series Topics in Heterocyclic Chemistry presents critical reviews on present and future trends in the research of heterocyclic compounds. Overall the scope is to cover topics dealing with all areas within heterocyclic chemistry, both experimental and theoretical, of interest to the general heterocyclic chemistry community. The series consists of topic related volumes edited by renowned editors with contributions of experts in the field. All chapters from Topics in Heterocyclic Chemistry are published Online First with an individual DOI. In references, Topics in Heterocyclic Chemistry is abbreviated as Top Heterocycl Chem and cited as a journal.
4-Fluoroprolines: Conformational Analysis and Effects on the Stability and Folding of Peptides and Proteins -- Silaproline, a silicon-containing proline surrogate -- Proline Methanologues - Design, Synthesis, Structural Properties, and Applications in Medicinal Chemistry -- Structure and Synthesis of Conformationally Constrained Molecules Containing Piperazic Acid -- Aminolactam, N-aminoimidazolone and N-aminoimdazolidinone peptide mimics -- Azepinone-Constrained Amino Acids in Peptide and Peptidomimetic Design -- Polyhydroxylated cyclic delta amino acids: Synthesis and conformational influences on biopolymers -- Thiazoles in Peptides and Peptidomimetics -- Advances in Merging Triazoles with Peptides and Proteins.
Keywords: Chemistry, Organic; Medicinal chemistry; Biotechnology; Organic Chemistry; Medicinal Chemistry; Chemical Bioengineering